Combined – whole blood and skin fibroblasts- transcriptomic analysis in Psoriatic Arthritis reveals molecular signatures of activity, resistance and early response to treatment - Grivas, Alexandros; Grigoriou, Maria; Malissovas, Nikos; Sentis, George; Filia, Anastasia; Flouda, Sofia; Katsimpri, Pelagia; Verginis, Panayotis; Boumpas, Dimitrios T. (Frontiers in Immunology, 2022)
Background An interplay between immune cells and resident skin and joint stromal cells is implicated in psoriatic arthritis (PsA), yet the mechanisms remain elusive with a paucity of molecular biomarkers for activity and response. Combined transcriptomic and immunophenotypic analysis of whole blood and skin fibroblasts could provide further insights. Methods Whole blood RNA-seq was performed longitudinally in 30 subjects with PsA at the beginning, one and six months after treatment, with response defined at six months. As control groups, 10 healthy individuals and 10 subjects with rheumatoid arthritis (RA) were recruited combined with public datasets from patients with psoriasis (PsO) and systemic lupus erythematous (SLE). Differential expression analysis and weighted gene co-expression network analysis were performed to identify gene expression signatures, while deconvolution and flow cytometry to characterize the peripheral blood immune cell profile. In a subset of affected and healthy individuals, RNA-seq of skin fibroblasts was performed and subjected to CellChat analysis to identify the blood-skin fibroblast interaction network. Results PsA demonstrated a distinct “activity” gene signature in the peripheral blood dominated by TNF- and IFN-driven inflammation, deregulated cholesterol and fatty acid metabolism and expansion of pro-inflammatory non-classical monocytes. Comparison with the blood transcriptome of RA, PsO, and SLE revealed a “PsA-specific signature” enriched in extracellular matrix remodeling. This was further supported by the skin fibroblast gene expression profile, displaying an activated, proliferating phenotype, and by skin-blood interactome analysis revealing interactions with circulating immune cells through WNT, PDGF and immune-related semaphorins. Of note, resistance to treatment was associated with upregulation of genes involved in TGFβ signaling and angiogenesis and persistent increase of non-classical monocytes. Differentially expressed genes related to platelet activation and hippo signaling discriminated responders and non-responders as early as one month after treatment initiation. Conclusion Transcriptome analysis of peripheral blood and skin fibroblasts in PsA reveals a distinct disease activity signature and supports the involvement of skin fibroblasts through their activation and interaction with circulating immune cells. Aberrant TGFβ signaling and persistently increased non-classical monocytes characterize treatment-resistant PsA, with pro-inflammatory pathways related to platelet activation and Hippo signaling predicting early response to treatment.